Modeling the Potential Impact of the 2014 American Academy of Pediatrics Respiratory Syncytial Virus Prophylaxis Guidance on Preterm Infant RSV Outcomes. Issue 4 (December 2015) - McLaurin, Kimmie; Chatterjee, Archana; Makari, Doris
Abstract Introduction The American Academy of Pediatrics (AAP) Committee on Infectious Diseases issued updated guidance on respiratory syncytial virus (RSV) prophylaxis in 2014. This report models the potential impact of the new guidance on RSV outcomes in preterm infants 29–34 weeks' gestational age (wGA) without chronic lung disease in the United States. Methods The number of preterm infants was estimated using 2012 natality data. Palivizumab utilization prior to the 2014 guidance update was estimated using 2013–2014 specialty pharmacy utilization data. Low, moderate, and high RSV hospitalization (RSVH) rates as well as average hospital length of stay, intensive care unit (ICU) admissions and mechanical ventilation (MV) frequencies were derived from published observational studies. Palivizumab efficacy was derived from two randomized clinical trials. RSV events that would be attributable to the 2014 guidance change were calculated for preterm infants 29–31 and 32–34 wGA. Results Annual number of infants 29–34 wGA surviving the neonatal period was estimated at 123, 687. Of these, an estimated 44, 712 (37%) would receive palivizumab based on the 2012 guidance. The annual number of RSVH among infants 29–34 wGA would increase from 3580 under the 2012 guidance to 6166 under the 2014 guidance based on moderate rates. This would result in an additional 24, 440 hospitalization days, 1162 ICU admissions, and 584 MV events among this population. Conclusions Based on published historical and contemporary data on RSVH rates in preterm infants 29–34 wGA, the 2014 AAP guidance is expected to result in additional burden to the healthcare system and families of preterm infants. The impact of the new guidance will be difficult to detect among the overall infant population, particularly in settings without routine testing for RSV, but the impact will be substantial for the small high-risk population affected by the changes. Funding AstraZeneca.